Comparison of Menstrual Symptoms in University Students with and without Female Genital Mutilation/Cutting - Altunkurek ŞZ; Yeşilyurt E; Hassan Mohamed S (Dove Medical Press, 2024)
Şeyma Zehra Altunkurek,1 Eylül Yeşilyurt,2 Samira Hassan Mohamed3 1Department of Public Health Nursing, University of Health Sciences, Gulhane Faculty of Nursing, Ankara, Türkiye; 2Department of Public Health Nursing, Ufuk University School of Nursing, Ankara, Türkiye; 3Department of Nursing, University of Health Sciences, Somalia Mogadishu Recep Tayyip Erdoğan Faculty of Health Sciences, Mogadishu, SomaliaCorrespondence: Samira Hassan Mohamed, Email samirahsn1992@gmail.comPurpose: The aim of this study was to compare the menstrual symptoms and dysmenorrhea in university students who underwent Female genital mutilation/cutting (FGM/C), in Mogadishu, Somalia, and students who did not undergo FGM/C in Ankara, Türkiye.Methods: A comparative cross-sectional study design was used.Results: Among the participants with FGM/C, 88.5% were Type 1 and the age at FGM/C was 8 years. The pain severity was 6.20± 2.54 in women with FGM/C and was higher than that of those without FGM/C (5.97± 2.32), but no significant difference was found. Among those who had FGM/C, 66% had a menstrual duration of 3- 5 days, while 52.0.% of those who did not have FGM/C had a menstrual duration of 6- 8 days (p< 0.05). While 85.1% of those without FGM/C had a menstrual cycle of 21- 35 days, 35% of those with FGM/C had a menstrual cycle of less than 20 days (p< 0.05). It was found that 95% of those who have undergone female circumcision and 90.2% of those who have not had dysmenorrhea (p< 0.05). Painkillers were always used by 28% of women with FGM/C and 26.3% of women without FGM/C (p< 0.05). The total MSS score of those who have not had FGM/C was 3.34± 0.72 and the score of those who have had FGM/C was 2.91± 0.74 (p< 0.05). The negative effects sub-dimension score was found to be higher in the non-FGM/C group with 3.20± 0.75, while the coping methods sub-dimension score was higher in the FGM/C group with 2.91± 1.13 (p< 0.05).Conclusion: FGM/C is still common in Somalia. Our study results showed that having FGM/C may cause differences in dysmenorrhea and menstrual symptoms. Efforts to increase students' effective coping with menstrual symptoms and dysmenorrhea are thought to be useful.Keywords: female genital mutilation, menstrual symptoms, university students, Somalia, Turkey